Corporate governance and financial performance: an empirical analysis of selected multinational firms in Nigeria - Gideon Tayo Akinleye; Odunayo Magret Olarewaju; Bamikole Samson Fajuyagbe (Problems and Perspectives in Management, 2019)
This study focused on corporate governance and performance of selected Nigerian multinational firms from 2012 to 2016. Specifically, the study focused on the effect of board size, activism and committee activism on return on asset and firm growth rate. Secondary data collected from four multinational firms were analyzed via static panel estimation techniques. While board size and board activism exerted significant negative impact on return on asset, committee activism exerted insignificant impact. The results of the study further showed that board size and board activism exert insignificant negative impact on firm’s growth rate, while committee activism insignificantly spurs firm’s growth rate. Decisively, discoveries from this study reflect that corporate governance has significant negative impact on return on asset, but has insignificant influence on the growth rate of Nigerian multinational firms. Based on these findings, the authors recommended that corporate governance dynamics in firms world over should be reconsidered, such that it gives credence to more than just numbers of persons or meetings held, but the main reasons and deliberations in such meetings. It was also recommended that excessive increase in magnitude or frequency of meetings held by board of directors cum committee should be avoided.